Understanding factors responsible for the slow decline of soil-transmitted helminthiasis following seven rounds of annual mass drug administration (2012-2018) among school children in endemic counties of Kenya: A mixed method study. - Janet Masaku; Collins Okoyo; Sylvie Araka; Rosemary Musuva; Elizabeth Njambi; Doris W Njomo; Charles Mwandawiro; Sammy M Njenga (Public Library of Science (PLoS), 2023)
Background Soil-transmitted helminthiasis (STH) continue to be a significant health problem in Sub-Saharan Africa especially among school children. In Kenya, treatment of over five million children has been conducted annually in 28 endemic counties since the year 2012. However, the latest monitoring and evaluation (M&E) results indicated a slow decline of prevalence and intensity of STH in some counties after the seven rounds of annual mass drug administration (MDA). The current study sought to determine the factors associated with the slow decline in prevalence and intensity of STH among school children participating in the school deworming programme. Methodology Mixed methods cross-sectional study was conducted in three endemic counties of Kenya. For quantitative technique, simple random sampling was used to select 1,874 school children from six purposively selected primary schools. The school children were interviewed, and a single stool collected and analysed using Kato-Katz technique. While for qualitative methods, 15 focus group discussions (FGDs) were conducted with purposively selected parents/guardians of school children. Data was collected through voice records using FGD and analyzed using NVIVO. Findings Prevalence of any STH infection was 30.8% (95%CI: 28.7-32.9), with the highest prevalence observed in Vihiga County (40.7%; 95%CI: 37.4-44.4). Multivariable analysis revealed that geographical location (OR = 3.78, (95%CI: 1.81-7.88) p<0.001), and not washing hands after defecation (OR = 1.91, (95%CI: 1.13-3.20) p = 0.015) were significantly associated with any STH infection. For qualitative analysis, majority of the parents/guardians of SAC felt that poor water sanitation and hygiene practices (WASH) both in school and household level could be a cause of continued STH infection. Also failing to include the rest of the community members in the MDAs were mentioned as possible contributors to observed slow decline of STH. Conclusions There was moderate STH prevalence and mean intensity despite the seven rounds of repeated annual MDA. The study recommends a revamped awareness creation on WASH and community wide treatment.